Meningkatkan Kepuasan Pelanggan Hotel Melalui Layanan Front Office Berkualitas, Harga, Dan Customer Experience: Studi Empiris Pada Hotel Horison Kotaraja, Papua - Pandan Setiadi; Indra Fahrizal (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the influence of front office service quality, price perception, and customer experience on customer satisfaction at the Horison Kotaraja Hotel Papua. This research method uses a quantitative approach with multiple linear regression analysis, using primary data obtained from 150 respondents using an online questionnaire. The results showed that the three variables had a significant positive effect on customer satisfaction. Price perception is the most dominant variable in influencing customer satisfaction, followed by customer experience and front office service quality. These findings provide the importance for hotel management to improve customer satisfaction through the right pricing strategy, consistent frontliner service, and creating a memorable customer experience.